A clinical study of the spectrum of gastro intestinal perforation peritonitis in a tertiary care centre - D., Dharamdev; Mascarenhas, Rupa Merlyn; Kumar, Arun (International Surgery Journal, 2021)
Background: Acute abdomen is one of the most common causes of emergencies which present to surgeon. Gastrointestinal perforation is third most common cause for emergency explorative laparotomy. Most of the time when patient presents to the tertiary centre, it is by clinical examination and investigation a diagnosis of perforation is established. The objective of the study was to evaluate causes, signs and symptoms, various modalities of management and possible complications which develop in gastrointestinal perforations. Methods: 50 patients with features of perforation were chosen using purposive sampling technique. Descriptive statistics was used for analysis. Detailed history was taken, physical examination and relevant investigations were done and correlated with intra operative and histopathology report wherever possible and followed up for complications. Results: Duodenal perforation was the most common cause of perforation accounting for 32 out of 50 cases. Surgical site infection was common complication accounting for 14 out of 50 cases. Conclusions: Surgery remains mainstay in all perforations.